Peer Group Mempengaruhi Kepatuhan Berobat Lansia Hipertensi - Ida Farida; Ni Putu Ariani (Poltekkes Kemenkes Bandung, 2012)
Estimated that in 2020 the number of elderly in Indonesia around 30 million. Approximately 30-60 percent of the elderly may have hypertension.In elderly, hypertension is a major risk factor for the occurrence of complications of a heart attack, stroke, and kidney failure.To avoid the complications required compliance of elderly to modify lifestyle, such as anti-hypetensive medication, exercise, and regular blood pressure control.One of methods to facilitate the compliance of treatment of client was peer group. This study aimed to examine the influence of the peer group to compliance of treatment hypetension in elderly. This study used a quasi-experimental design with an intervention group and a control group. Respondents in the intervention group were divided into two small groups of 9-11 people. Peer group activities carried out once a week, for 6 weeks.The control group was given treatment in generally health education on treatment compliance of service standards of Posbindu.Treatment compliance was measured by attendance at posbindu, reducing salt, and regular exercise.The results showed that the intervention of peer group were significantly influence to comply hypertension treatment on elderly.Elderly hypertension followed peer group activities to comply with its management program so that the blood pressure of them could be lowered close to normal values (140/90 mmHg)